Study of ultrathin SiO2 Interlayer wafer bonding for heterogeneous III–V/Si photonic integration. (11th September 2015) - Lee, Chee-Wei; Liang, Ying Shun; Ng, Doris Keh-Ting; Yang, Yi; Hnin, Yu Yu Ko; Wang, Qian
Abstract: We demonstrated low-temperature bonding of III–V InP-based compound semiconductor on silicon via nano-thin SiO2 interlayer down to thickness of 20 nm, with ultra-smooth surface for heterogeneous photonic integration. The bonding is achieved with chemical cleaning of the sample surface, followed by oxygen plasma surface activation, which gives high quality bonding between the two different materials. Detail analyses on the bonded samples are carried out. From the photoluminescence and the x-ray diffraction measurements, in which no significant peak shift and peak broadening are observed, we conclude that the crystalline quality of the bonded thin film is preserved. The cross-sectional high resolution transmission electron microscopy shows that bonded III–V-SiO2 –Si interface has no observable defect. These results reinforce that the proposed bonding offers a promising technology for realizing versatile heterogeneous photonics integration.